Palliative Care for a Mentally Incompetent End Stage Renal Failure Patient: Why Is It Important? - Chan, Kwok-Ying (Case Rep Nephrol, 2015)
People with intellectual disabilities are among the most disadvantaged groups in society. Here we report a mentally incompetent end stage renal failure (ESRF) patient with frequent emergency visits who made a significant improvement in symptoms control and reduction in casualty visits after introduction of renal palliative care service. Multidisciplinary approach would be useful in this case.